EVALUATION OF RAPESEED STALK PARTICLEBOARD BONDED WITH LABORATORY-MADE UREA-FORMALDEHYDE RESIN - Yong-Sung Oh; Mohd Ariff Jamaludin (Ciência Florestal, 2015)
BrassicanapusL. (rapeseed) stalk was used as a possible raw material for particleboard. A urea-formaldehyderesin was synthesized in the laboratory with resin solids at 50% content as a particleboard binder. Thephysical characteristics of the synthesized urea-formaldehyde resin were analyzed for solid content, specificgravity, viscosity, gel time, pH, and free formaldehyde content. The laboratory particleboards were madeusing rapeseed stalk and wood particles based on a rapeseed stalk oven dry weight of 0, 23, 48, 73, and100% with UF resin. The physical and mechanical properties of the particleboards were tested according tothe ASTM D 1037-99 procedure. The internal bond, bending strength and screw-holding properties of theparticleboards made using the urea-formaldehyde resin decreased gradually with increasing rapeseed stalkcontent. However, the acceptable physical and mechanical properties of all the particleboards demonstratedthat rapeseed stalk is a suitable raw material for particleboard manufacture.